PENGARUH PROMOSI DAN PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA TOKO BNJ ELEKTRONIK KOTA LUBUKLINGGAU - Ronal Aprianto (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2016)
Effect of Promotion and Service to the Customer Satisfaction HSD Electronic Stores Lubuklinggau. The purpose of this study was to determine the effect of Promotion and Service to the Customer Satisfaction HSD Electronic Stores Lubuklinggau. The population in this research were as many as 885 customers and the sample in this study amounted to 88 respondents. The data collection technique using a questionnaire (questionnaire) that have been tested beforehand using validity and reliability test. Data analysis technique used is the classical assumption (normality test, and test liniearitas), multiple linear regression, determination and F test where researchers using SPSS version 20. The linear regression equation obtained positive value is Y = 18.324 + 0,316X1 + 0,370X2. Values obtained amounted constants a = 18.324 units, variable regression coefficients Promotion obtained at b1 = 0,316 units, variable regression coefficients Services obtained for b2 = 0.370 units. Determinant coefficient value (R2¬) acquired, amounted to 0.443, can be interpreted that the variation of the dependent variable value changes Customer satisfaction can be explained by all the variables are non-Promotion and Service together (simultaneously) by 44.3% and the balance of 55, 7% is influenced by other variables such as, product prices, interest in buying, product quality, state of the economy and so forth. The conclusion that: the F test results obtained value of F = 33.771> F table = 3.10 significance level simultaneously and significantly F was 0,000. Attested and accepted hypotheses.Key Words : Promotion and Service, Customet Satisfaction.